Peningkatan Hasil Belajar PPKn Melalui Model Pembelajaran Kooperatif Tipe JIGSAW Pada Siswa Kelas IX-3 SMP Negeri 2 Tanete Riaja Kabupaten Barru - Rahman, Rahman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This research is a class action research (Classroom Action Research) which aims to improve the learning outcomes of Civics through jigsaw type cooperative learning models in Class IX-3 students of SMP Negeri 2 Tanete Riaja Barru Regency. The subjects of this research were Class IX-3 students in odd semester 2019/2020 as many as 25 students. Data collection techniques used were the final Cycle I test, the final Cycle II test, and the observation sheet. The results obtained from the quantitative and qualitative descriptive analysis are as follows: The average score of student learning outcomes after taking action in Cycle I is 68.97%. with an attendance rate of 99%, the courage of students working on the questions on the board is 35%. After continuing in Cycle II, the average score of student learning outcomes on the Pancasila and Citizenship Education subject matter was 77.27% with an attendance rate of 99.17%, the courage to answer questions on the board 43%. The foregoing indicates that an increase in learning outcomes for Pancasila Education and Citizenship for Class IX-3 students of SMP Negeri 2 Tanete Riaja Barru Regency after applying the jigsaw type cooperative learning model. The motivation of students in participating in the teaching and learning process increased, this was seen from the increase in the frequency of students who wanted to solve practice questions on the board, the seriousness of students in the use of instructional media, and student activity in each group work.